TEMUKAN PASSIONMU DALAM DUNIA KERJA - Liswandi Liswandi (JURNAL ABDIMAS PLJ, 2022)
Passion related to work may make us forget that the work done is for someone else, so that any given task will be completed easily. Without passion, someone will not find ease in his work because we are not happy with what we are doing now. The purpose of this webinar activity is to share knowledge about how to find passion in the world of work with university students, high school students, and the general public. For the webinar method given, it is done by conducting presentations and discussion questions and answers. The Zoom application is used to present material to participants. This webinar provides an overview to participants that passion actually plays an important role in the world of work from our point of view as workers and also that the passion of workers who are fully supported either by the company or by individuals will make work performance higher above average. Keywords : Passion, work, performance